1999
DOI: 10.1007/s002130050962
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of plasma tryptophan availability to course of illness and clinical features of alcoholism: a preliminary study

Abstract: These data suggest that a low plasma TRYP/LNAA ratio is associated with susceptibility to anxiety, antisocial-type personality characteristics, and an early age of onset for alcoholism. In contrast, a high plasma TRYP/LNAA ratio is associated with a later onset of alcoholism and dysphoria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…effectiveness as adjunctive treatment to cognitive behavioral therapy in early and late onset alcoholics was presented at a meeting of the American Society of Addiction Medicine (Johnson et al 1999). These data showed that ondansetron (particularly 4 µg/kg b.i.d) was significantly superior to placebo in reducing alcohol drinking and increasing abstinence rates among early but not late onset alcoholics.…”
Section: -Ht 3 Antagonistsmentioning
confidence: 92%
See 2 more Smart Citations
“…effectiveness as adjunctive treatment to cognitive behavioral therapy in early and late onset alcoholics was presented at a meeting of the American Society of Addiction Medicine (Johnson et al 1999). These data showed that ondansetron (particularly 4 µg/kg b.i.d) was significantly superior to placebo in reducing alcohol drinking and increasing abstinence rates among early but not late onset alcoholics.…”
Section: -Ht 3 Antagonistsmentioning
confidence: 92%
“…Broken lines indicate reduced function. Solid lines represent normal function who have an early alcoholism onset, compared with those who develop the disease in later life, are more prone to serotonergic dysfunction (Ballenger et al 1979;BuydensBranchey et al 1989;Vikkunen andLinnoila, 1990, 1997;Fils-Aime et al 1996;George et al 1999;Swann et al 1999). While this 5-HT dysfunction among EOA has been postulated to be a deficiency state (LeMarquand et al 1994a(LeMarquand et al , 1994b, our results would argue for a more fundamental and complex interaction between mechanisms controlling serotonin regulation at the transporter and their interaction with drinking (see Fig.…”
Section: -Ht 3 Antagonistsmentioning
confidence: 97%
See 1 more Smart Citation
“…Among EOAs (who reported more frequent incarceration for violent crimes, more suicide attempts, and more frequent depression than LOAs), central serotonergic activity (i.e., measured as the ratio of plasma tryptophan to other amino acids competing for brain entry) was inversely related to depression and aggression. Swann et al (1999) found that individuals with low activity on this measure of serotonergic function were more anxious and had antisocial personality characteristics and an early age of onset of alcoholism. In another sample of recently abstinent alcoholics, EOAs also had a more severe course of alcoholism and a lower mean cerebrospinal fluid concentration of 5-hydroxyindoleacetic acid, the major serotonin metabolite, than LOAs (Fils-Aime et al 1996).…”
Section: Introductionmentioning
confidence: 87%
“…In the case of quinolinic acid neurotoxicity will be increased, whereas neuroprotection will be afforded by kynurenic acid (see Fig. 2) [85][86][87][88][89][90][91][92][93]. Abuse of alcohol will also impair the effectiveness of hepatic tryptophan pyrrollase, an effect which will be exacerbated in chronic problem drinkers, due to increasing liver damage, and may be implicated in the neurocognitive deficits associated with alcohol dependency [94][95][96].…”
Section: Neurochemistrymentioning
confidence: 99%